Respiration of aged soil carbon during fall in permafrost peatlands enhanced by active layer deepening following wildfire but limited following thermokarst. (13th August 2018) - Estop-Aragonés, Cristian; Czimczik, Claudia I; Heffernan, Liam; Gibson, Carolyn; Walker, Jennifer C; Xu, Xiaomei; Olefeldt, David
Abstract: Permafrost peatlands store globally significant amounts of soil organic carbon (SOC) that may be vulnerable to climate change. Permafrost thaw exposes deeper, older SOC to microbial activity, but SOC vulnerability to mineralization and release as carbon dioxide is likely influenced by the soil environmental conditions that follow thaw. Permafrost thaw in peat plateaus, the dominant type of permafrost peatlands in North America, occurs both through deepening of the active layer and through thermokarst. Active layer deepening exposes aged SOC to predominately oxic conditions, while thermokarst is associated with complete permafrost thaw which leads to ground subsidence, inundation and soil anoxic conditions. Thermokarst often follows active layer deepening, and wildfire is an important trigger of this sequence. We compared the mineralization rate of aged SOC at an intact peat plateau (∼70 cm oxic active layer), a burned peat plateau (∼120 cm oxic active layer), and a thermokarst bog (∼550 cm anoxic peat profile) by measuring respired 14 C–CO2 . Measurements were done in fall when surface temperatures were near-freezing while deeper soil temperatures were still close to their seasonal maxima. Aged SOC (1600 yrs BP) contributed 22.1 ± 11.3% and 3.5 ± 3.1% to soil respiration in the burned and intact peat plateau, respectively, indicating a fivefold higher rate of aged SOC mineralization in the burned than intact peat plateau (0.15 ± 0.07 versus 0.03 ± 0.03 g CO2 –C m −2 d −1 ). None or minimal contribution of aged SOC to soil respiration was detected within the thermokarst bog, regardless of whether thaw had occurred decades or centuries ago. While more data from other sites and seasons are required, our study provides strong evidence of substantially increased respiration of aged SOC from burned peat plateaus with deepened active layer, while also suggesting inhibition of aged SOC respiration under anoxic conditions in thermokarst bogs.